Konflik Batin Tokoh Utama Jintan dalam Anime Anohana (Teori Konflik Kurt Lewin) - Nurul Haitami; Ayu Putri Seruni (Jurnal Bahasa Jepang Taiyou, 2022)
Anime Ano Hi Mita Hana no Namae wo Bukutachi wa Mada Shiranai tells the story of the main character Jintan who is always followed by the haunting ghost of Menma, one of his childhood friends. The fact that Menma is dead, Menma should not be in front of Jintan. Besides that fact, there are many things that make Jintan believe in the existence of Menma's ghost. The many inner conflicts experienced by the main character Jintan make the writer interested in conducting research on this theme according to Kurt Lewin's conflict theory. This study uses the method of content analysis, from a study of the existing literature with the note-taking technique. The result of this study is that Jintan's character who experiences inner conflict is more likely to lead to type 1 conflict, namely the approach-avoidance conflict. It is called that because the character Jintan, who is still in the shadows of the obscurity of Menma's existence, also likes the existence of Menma himself who is always by his side.